Identification of the most common predatory hoverflies of Mediterranean vegetable crops and their parasitism using multiplex PCR - Gomez-Polo, PRISCILA GOMEZ; POLO, PRISCILA GOMEZ; Traugott, Michael; Alomar, Oscar; Castane, Cristina; Rojo, Santos; Agusti, Nuria (My University, 2014)
The larvae of many hoverflies (Diptera: Syrphidae) are important polyphagous predators used in integrated pest management programs. Because the accurate identification of preimaginal stages by morphological characters is difficult, we have developed a multiplex PCR to identify the immature and/or adult stages of the most common syrphid species in Mediterranean vegetable crops: Episyrphus balteatus, Scaeva pyrastri, Eupeodes corollae, Meliscaeva auricollis, Sphaerophoria scripta, and Sphaerophoria rueppellii. The latter two species were amplified by the same primer pair due to the high similarity of their cytochrome oxidase subunit I sequences. Additionally, the assay included a primer pair targeting Diplazon laetatorius, a common koinobiont ichneumonid endoparasitoid of predatory syrphid larvae. The multiplex PCR assay proved to be highly specific and sensitive, and it was used to study the assemblage of hoverfly species in larval stage in two Mediterranean lettuce crops in two consecutive years. The molecular analysis revealed that Eu. corollae, Ep. balteatus, and Sph. scripta/Sph. rueppellii were the species present in the investigated fields. Species composition differed depending on sampling date and whether the larvae were collected on the plants or on the ground. The parasitoid D. laetatorius was not detected in any of the analyzed hoverfly larvae, suggesting low-parasitism pressure in the studied syrphid populations. The wide distribution of most of these syrphid species makes this multiplex PCR assay an ideal tool to deepen our knowledge on the ecology of these polyphagous hoverfly species in preimaginal stages and to improve the use of hoverflies to control insect pests.